Ovarian Torsion Masquerading As Appendicitis In A Nine Year Old Child-A Case Report - Sowmya M; Shwetha Shashidhar; Trishuli BP (International Journal of Medical Research and Review, 2014)
Ovarian torsion is an infrequent diagnosis in the pediatric age group. The clinical picture is nonspecific in children, which often makes the diagnosis a challenge. We present a case of a nine year old girl who presented with a two day history of fever, vomiting and acute abdominal pain. Initial diagnosis of acute appendicitis was made, however, on operative exploration, she was found to have a right adnexal torsion and detorsion was done. Ovarian torsion should be considered as differential diagnosis in pediatric and adolescent females presenting with abdominal pain. However, early recognition and prompt management yield significant reduction in morbidity and an increased likelihood of ovarian salvage to maximize the future reproductive potential.